(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Dementia caused by cancer is a significant health issue that affects the cancer survivors, particularly those survivors who have undergone radiation therapy and chemotherapy. This condition can lead to cognitive impairment and a decline in quality of life. Furthermore, the influence of cancer-related dementia on mortality rates is not well understood. This systematic review and meta analysis aimed to investigate the association between cancer-related dementia and mortality. Our findings suggest that cancer-related dementia is associated with increased mortality among cancer survivors. This highlights the need for improved screening and management of cognitive impairment among cancer patients, particularly those at higher risk of developing dementia.